Dye-based polaroid for nylon polarized glasses and preparation method of dye-based polaroid
By adopting characteristic stacking structure and processing technology in polarizing lenses, the problem of TAC and PA materials falling off and difficult to control process is solved, and the effective casting and process simplification of PA resin is achieved, and UV glue and PA optical grade are avoided. The use of films reduces production costs.
Patent Information
- Application Number
- CN202411389743.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-01
- Publication Date
- 2024-12-13
AI Technical Summary
The TAC and PA materials of existing polarizing eyeglasses are easy to fall off and the process is difficult to control. Especially the UV glue process used for bonding UV glue and PA requires increased UV light irradiation, and PA optical-grade films are expensive.
A dye-based polarizer for nylon polarizing glasses is adopted, including a release film, an acrylic layer, an upper TAC layer, a PVA layer and a lower TAC layer stacked from top to bottom. The acrylic layer has a specific acid value and TG Temperature, thickness and creep value, without using UV glue and PA optical grade film, acrylic glue is obtained by cross-linking isocyanate curing agent and epoxy curing agent, and processed with PVA coil to form a TAC layer, and then release the The film is coated with acrylic glue.
Effective casting and molding of TAC and PA resins is achieved, avoiding layered shedding at the interface, simplifying the process flow, and reducing production costs.
Smart Images

Figure CN119119897A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polarizing films, and in particular to a dye-based polarizing film for nylon polarized glasses and a preparation method thereof. Background Art
[0002] Sunlight shining on sand, water, road and snow can easily produce reflected glare. According to the Fresnel principle, when the angle between the reflected light and the horizontal plane is small, most of the reflected light is polarized light reflected to the human eye. At the same time, because ordinary sunlight contains ultraviolet light, this type of light is harmful to the human eye. Therefore, in order to absorb the polarized light reflected into the human eye, polarizers are used in the production process of eyeglasses to bond or injection mold with other resins to produce polarized sunglasses.
[0003] Early polarized eyeglasses were mainly made by injection molding and laminating TAC (triacetate film) on both sides of the polarizer. However, due to the water resistance and price of TAC, eyeglass manufacturers used UV glue to laminate PC (polycarbonate) on TAC, and then injected and bent it with PC resin to obtain it. With the development of nylon film materials, this material has the properties of high light transmittance and low water permeability, and the flexibility of this material is better than PC, and it is not easy to crack during the bending process. Therefore, PA (polyamide) resin is expected to replace PC as a common material for eyeglasses. Currently, TAC is directly injected with PA resin, but due to the difference in the properties of TAC and PA materials, the contact point of the two layers of material is easy to fall off, and the use scenario is limited. The second solution is to first use PA optical film and polarizing film to bond with UV glue, and then bend it with PA resin material. There are two problems with this solution. One is that the UV glue used for bonding UV glue and PA requires increased UV light exposure, and the process is difficult to control. The second problem is that PA optical-grade film is currently expensive. Summary of the invention
[0004] The technical problem to be solved by the present invention is to overcome the defects of the existing polarized glasses, such as TAC and PA materials that are easy to fall off and delaminate, are expensive and difficult to control the process, and propose a dye-based polarizer for nylon polarized glasses and a preparation method thereof. The prepared polarizer does not require UV glue or PA optical-grade film, and can be effectively cast with PA resin without delamination at the interface, and the process is simple.
[0005] In order to solve the above technical problems, the present invention proposes the following technical solutions: A dye-based polarizer for nylon polarized glasses, comprising a release film, an acrylic adhesive layer, an upper TAC layer, a PVA layer and a lower TAC layer stacked in sequence from top to bottom;
[0006] The acrylic adhesive layer has the following properties:
[0007] 1. The acid value of the acrylic adhesive layer is less than 0.05;
[0008] 2. The TG temperature of the acrylic adhesive layer is -20℃ to -8℃;
[0009] 3. The thickness of the acrylic adhesive layer is 5-25um;
[0010] When the thickness is 5-10um, the creep value is less than 0.2mm / 1000S; when the thickness is 10-15um, the creep value is 0.3mm / 1000s; when the thickness is 15-20um, the creep value is 0.38mm / 1000s; when the thickness is 20-25um, the creep value is ≤0.45mm / 1000s; the creep value test method refers to the national standard GB: 7750-87, the temperature is 25℃, the test time is 1000s, and the load is 2KG;
[0011] 4. The gel fraction of the acrylic adhesive layer is greater than 75%.
[0012] The above technical solution is further limited in that a lower acrylic adhesive layer is provided below the lower TAC layer, which has the same properties as the acrylic adhesive layer above the upper TAC layer; a protective film is provided below the lower acrylic adhesive layer, and the base material used is a PE protective film or a PP protective film.
[0013] The above technical solution is further limited in that the acid value of the acrylic adhesive layer is less than 0.02 and the thickness is 10-15 um.
[0014] The above technical solution is further limited in that the thickness of the release film is 30-80 um, and the material used is a base material PE material.
[0015] The above technical solution is further limited in that the thickness of the upper TAC layer and the lower TAC layer is 80-120um, and the water permeability is 800-1500g / m 2 , UV absorption at 380nm is less than 0.5%; the thickness of the PVA layer is 25-35um.
[0016] In order to solve the above technical problems, the present invention proposes the following technical solutions: A method for preparing a dye-based polarizer for nylon polarized glasses, comprising the following steps:
[0017] Step 1: cross-linking an acrylic raw resin having a number average molecular weight greater than 120W and a PDI distribution of 2-6 by using an isocyanate curing agent and / or an epoxy type curing agent to obtain an acrylic glue having a viscosity of 1200-1500 and a tested gel fraction of 68-83%;
[0018] The PVA coil is unrolled, expanded, dyed, stretched, color-corrected, and dried to obtain the PVA element;
[0019] Step 2: Compound TAC above and below the PVA element to form an upper TAC layer and a lower TAC layer respectively;
[0020] Step 3: Apply the acrylic glue in step 1 on the release film and compound it with the upper TAC in step 2 to obtain the dye-based polarizer for nylon polarized glasses.
[0021] In order to solve the above technical problems, the present invention proposes the following technical solutions: A method for preparing a dye-based polarizer for nylon polarized glasses, comprising the following steps:
[0022] Step 1: cross-linking an acrylic raw resin having a number average molecular weight greater than 120W and a PDI distribution of 2-6 by using an isocyanate curing agent and / or an epoxy type curing agent to obtain an acrylic glue having a viscosity of 1200-1500 and a tested gel fraction of 68-83%;
[0023] The PVA coil is unrolled, expanded, dyed, stretched, color-corrected, and dried to obtain the PVA element;
[0024] Step 2: Compound TAC on the upper and lower parts of the PVA element to form an upper TAC layer and a lower TAC layer, and after compounding, compound the protective film on the lower part of the lower TAC layer with the acrylic glue in step 1;
[0025] Step 3: Apply the acrylic glue from step 1 on the release film, and then compound it on top of the upper TAC layer to obtain the dye-based polarizer for nylon polarized glasses.
[0026] The above technical solution is further limited in that, in step 1, the PDI distribution of the acrylic raw gum resin is 3-6.
[0027] The above technical solution is further limited in that, in step 1, the swelling tank uses deionized water at a temperature of 25-32°C; the dyeing tank contains a high dichroic dye solution at a temperature of 35-45°C, wherein the high dichroic dye includes one or more of yellow, red, and blue, the solubility of the dye solution is between 0.05% and 0.5%, and the solubility of the boric acid solution is between 0.9 and 4%; the solution in the stretching tank is a boric acid solution at a temperature of 50-65°C; the solution in the color-correcting tank is a boric acid solution at a temperature of 25-35°C.
[0028] The technical solution is further limited in that, in step 2, PVA hydrogel is used to compound TAC above and below the PVA element respectively, and the compounding temperature is between 50-85°C.
[0029] Compared with the prior art, the present invention has the following beneficial effects: the dye-based polarizer for nylon polarized glasses of the present invention does not use UV glue or PA optical-grade film, and can be effectively cast with PA resin without stratification or shedding at the interface, and the process is simple. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 It is a schematic structural diagram of the dye-based polarizer for nylon polarized glasses of the present invention.
[0031] Figure 2 It is a schematic structural diagram of another embodiment of the dye-based polarizer for nylon polarized glasses of the present invention. DETAILED DESCRIPTION
[0032] See also Figure 1 A dye-based polarizer for nylon polarized glasses comprises a release film 1, an acrylic adhesive layer 2, an upper TAC layer 3, a PVA layer 4 and a lower TAC layer 5 which are stacked in sequence from top to bottom.
[0033] The thickness of the release film 1 is 30-80 um, and the material used is a base material PE material.
[0034] The acrylic adhesive layer 2 has the following properties:
[0035] 1. The acid value of the acrylic adhesive layer is less than 0.05, preferably less than 0.02;
[0036] 2. The TG temperature of the acrylic adhesive layer is -20°C to -8°C, preferably greater than -15°C to -10°C;
[0037] 3. The thickness of the acrylic adhesive layer is 5-25um, preferably 10-15um; when the thickness is 5-10um, the creep value is less than 0.2mm / 1000S, and the load is 2kg; when the thickness is 10-15um, the creep value is 0.3mm / 1000s; when the thickness is 15-20um, the creep value is 0.38mm / 1000s; when the thickness is 20-25um, the creep value is ≤0.45mm / 1000s; the creep value test method refers to the national standard GB: 7750-87, the temperature is 25℃, the test time is 1000s, and the load is 2KG.
[0038] 4. The gel fraction of the acrylic adhesive layer is greater than 75%.
[0039] The thickness of the upper TAC layer 3 is 80-120um and the water permeability is 800-1500g / m 2 , preferably
[0040] 1000-1200g / m 2 , UV absorption at 380nm is less than 0.5%.
[0041] The thickness of the PVA layer 4 is 25-35 μm.
[0042] The thickness of the lower TAC layer 5 is 80-120um and the water permeability is 800-1500g / m 2 , preferably
[0043] 1000-1200g / m 2 , UV absorption at 380nm is less than 0.5%.
[0044] like Figure 2 As shown, in another embodiment, a lower acrylic adhesive layer 6 is further provided below the lower TAC layer 5 , and the material properties of the lower acrylic adhesive layer 6 are the same as those of the acrylic adhesive layer 2 .
[0045] A protective film 7 is further provided below the lower acrylic adhesive layer 6, and the base material used is a PE protective film or a PP protective film.
[0046] The method for preparing the dye-based polarizer for nylon polarized glasses comprises the following steps:
[0047] Step 1: crosslinking an acrylic raw resin having a number average molecular weight greater than 120W and a PDI (polydispersity index) distribution of 2-6 (preferably a PDI distribution of 3-6) by using an isocyanate curing agent and / or an epoxy type curing agent to obtain an acrylic glue having a viscosity of 1200-1500 and a tested gel fraction of 68-83%;
[0048] The PVA coil is unwound, swollen, dyed, stretched, color-corrected, and dried to obtain a PVA element (PVA layer 4); wherein the solutions and temperatures of each tank from front to back are as follows: the swelling tank uses deionized water at a temperature of 25-32°C; the dyeing tank contains a high dichroic dye aqueous solution at a temperature of 35-45°C, and according to different optical requirements, the high dichroic dye can be selected from one or a mixture of yellow, red, and blue, and the solubility of the dye solution is controlled between 0.05% (mass fraction) and 0.5%, and the solubility of the boric acid solution is controlled between 0.9% and 4%; the solution in the stretching tank is a boric acid solution at a temperature of 50-65°C; the solution in the color-corrected tank is a boric acid solution at a temperature of 25-35°C;
[0049] Step 2: Use PVA water glue to compound TAC above and below the PVA element (PVA layer 4) to form an upper TAC layer 3 and a lower TAC layer 5, respectively. The temperature of the compounding process is controlled between 50-85°C. After compounding, use the acrylic glue of step 1 to compound the PE protective film 7 below the lower TAC layer 5;
[0050] Step 3: Use a slit or micro-concave coating method to coat the acrylic glue in step 1 on the PP or PE release film 1, and then compound it on the upper TAC layer 3 to obtain the dye-based polarizer for nylon polarized glasses of the present invention.
[0051] Preparation Example 1
[0052] An acrylic resin material with a molecular weight of 130W and a PDI of 4.5 was selected, and an acrylic glue aqueous solution was prepared with ethyl acetate and a curing agent (isocyanate curing agent). The solution viscosity was 1230, and the creep value of the glue was 0.25 mm.
[0053] PVA (M6000) from Mitsubishi Chemical was selected and sequentially subjected to the steps of washing, swelling, dyeing, stretching, coloring and drying. The temperatures of the solutions in each tank were 27°C, 27°C, 31°C, 45°C, 30°C and 65°C respectively. The solubility of the dye solution in the dyeing tank was 0.3%, and the ratio of yellow: red: blue was 1:1.5:2.6. The solubility of the boric acid solution in the stretching tank was 2.0%, and the solubility of the boric acid solution in the coloring tank was 1.5%. PVA element was obtained.
[0054] PVA hydrogel is used to compound TAC above and below the PVA element (PVA layer 4) to form an upper TAC layer 3 and a lower TAC layer 5, respectively. The moisture permeability value of TAC is 1000g / m 2 Then, a PE protective film 7 is compounded under the lower TAC layer 5. The optical transmittance is measured to be 41.5%, and the polarization degree is 98, thereby obtaining a four-layer film material.
[0055] The prepared acrylic adhesive solution is coated on a release film 7 (e.g., a release film made of PP material), and then compounded with the above four-layer film material (specifically compounded on the upper TAC layer 3), and finally the obtained material is injection molded with PA resin to obtain a finished product. The finished product is tested for deformation over time, alkali resistance delamination test, bending test, and high temperature and high humidity performance.
[0056] Comparative Example 1
[0057] Comparative Example 1 is the same as Preparation Example 1, except that the PDI of the acrylic resin material is 9, and the glue creep value of the acrylic glue solution is 0.28 mm.
[0058] Comparative Example 2
[0059] Comparative Example 2 is the same as Preparation Example 1, except that the glue creep value of the acrylic glue solution is 0.5 mm.
[0060] Comparative Example 3
[0061] Comparative Example 3 is the same as Preparation Example 1, except that the moisture permeability of TAC is 300 g / m 2 .
[0062] Comparative Example 4
[0063] Comparative Example 4 is the same as Preparation Example 1, except that the moisture permeability of TAC is 2000 g / m 2 .
[0064] Table 1 is a comparison table of the test results of Preparation Example 1 and Comparative Examples 1-4.
[0065]
[0066] Table 1
[0067] The present invention has the following beneficial effects: the dye-based polarizer for nylon polarized glasses does not require UV glue or PA optical-grade film, and can be effectively cast with PA resin without delamination or shedding at the interface, and the process is simple.
Claims
1. A dye-based polarizer for nylon polarized glasses, It is characterized in that It includes a release film, an acrylic adhesive layer, an upper TAC layer, a PVA layer and a lower TAC layer stacked in sequence from top to bottom; The acrylic adhesive layer has the following properties:
1. The acid value of the acrylic adhesive layer is less than 0.05; 2. The TG temperature of the acrylic adhesive layer is -20℃ to -8℃; 3. The thickness of the acrylic adhesive layer is 5-25um; When the thickness is 5-10um, the creep value is less than 0.2mm / 1000S; when the thickness is 10-15um, the creep value is 0.3mm / 1000s; when the thickness is 15-20um, the creep value is 0.38mm / 1000s; when the thickness is 20-25um, the creep value is ≤0.45mm / 1000s; the creep value test method refers to the national standard GB: 7750-87, the temperature is 25℃, the test time is 1000s, and the load is 2KG; 4. The gel fraction of the acrylic adhesive layer is greater than 75%.
2. The dye-based polarizer for nylon polarized glasses according to claim 1, It is characterized in that A lower acrylic adhesive layer is provided below the lower TAC layer, and its properties are the same as those of the acrylic adhesive layer above the upper TAC layer. A protective film is provided below the lower acrylic adhesive layer, and its base material is a PE protective film or a PP protective film.
3. The dye-based polarizer for nylon polarized glasses according to claim 1, It is characterized in that The acid value of the acrylic adhesive layer is less than 0.02 and the thickness is 10-15um.
4. The dye-based polarizer for nylon polarized glasses according to claim 1, It is characterized in that The thickness of the release film is 30-80um, and the material used is base material PE material.
5. The dye-based polarizer for nylon polarized glasses according to claim 1, It is characterized in that The thickness of the upper and lower TAC layers is 80-120um, and the water permeability is 800-1500g / m 2 , UV absorption at 380nm is less than 0.5%; the thickness of the PVA layer is 25-35um.
6. A method for preparing a dye-based polarizer for nylon polarized glasses as claimed in claim 1, It is characterized in that The following steps are involved: Step 1: cross-linking an acrylic raw resin having a number average molecular weight greater than 120W and a PDI distribution of 2-6 by using an isocyanate curing agent and / or an epoxy type curing agent to obtain an acrylic glue having a viscosity of 1200-1500 and a tested gel fraction of 68-83%; The PVA coil is unrolled, expanded, dyed, stretched, color-corrected, and dried to obtain the PVA element; Step 2: Compound TAC above and below the PVA element to form an upper TAC layer and a lower TAC layer respectively; Step 3: Apply the acrylic glue in step 1 on the release film and compound it with the upper TAC in step 2 to obtain the dye-based polarizer for nylon polarized glasses.
7. A method for preparing a dye-based polarizer for nylon polarized glasses as claimed in claim 2, It is characterized in that The following steps are involved: Step 1: cross-linking an acrylic raw resin having a number average molecular weight greater than 120W and a PDI distribution of 2-6 by using an isocyanate curing agent and / or an epoxy type curing agent to obtain an acrylic glue having a viscosity of 1200-1500 and a tested gel fraction of 68-83%; The PVA coil is unrolled, expanded, dyed, stretched, color-corrected, and dried to obtain the PVA element; Step 2: Compound TAC on the upper and lower parts of the PVA element to form an upper TAC layer and a lower TAC layer, and after compounding, compound the protective film on the lower part of the lower TAC layer with the acrylic glue in step 1; Step 3: Apply the acrylic glue from step 1 on the release film, and then compound it on top of the upper TAC layer to obtain the dye-based polarizer for nylon polarized glasses.
8. The method for preparing the dye-based polarizer for nylon polarized glasses according to claim 6 or 7, It is characterized in that In step 1, the PDI distribution of the acrylic raw resin is 3-6.
9. The method for preparing the dye-based polarizer for nylon polarized glasses according to claim 6 or 7, It is characterized in that In step 1, the swelling tank uses deionized water at a temperature of 25-32°C; the dyeing tank contains a high dichroic dye solution at a temperature of 35-45°C, wherein the high dichroic dye includes one or more of yellow, red, and blue, the solubility of the dye solution is between 0.05% and 0.5%, and the solubility of the boric acid solution is between 0.9 and 4%; the solution in the stretching tank is a boric acid solution at a temperature of 50-65°C; the solution in the color-correcting tank is a boric acid solution at a temperature of 25-35°C.
10. The method for preparing the dye-based polarizer for nylon polarized glasses according to claim 6 or 7, It is characterized in that In step 2, PVA hydrogel is used to compound TAC above and below the PVA element, respectively, and the compounding temperature is between 50-85°C.
